TANTANGAN DAN PELUANG DALAM IMPLEMENTASI PENDIDIKAN INKLUSIF DI SDN 24 KECAMATAN PONTIANAK KOTA - Riennova, Riennova; Halidjah, Siti; Asrori, Muhammad (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
The City of Pontianak has designated all educational units, both public and private, as inclusive education providers. Public elementary schools, as educational units, face their own challenges and opportunities in implementing inclusive education programs. The presence of students with special needs (PDBK) in schools requires special attention from educators, considering that the teachers in these schools are elementary education teachers and not special education teachers. The purpose of this study is to describe the challenges and opportunities in implementing inclusive education at SD Negeri 24 in Pontianak City District.This research uses a descriptive qualitative method to analyze the challenges and opportunities in implementing inclusive education in elementary schools. The research sample includes classroom teachers, Special Assistant Teachers (GPK), students with special needs (PDBK), and parents. The instruments used were interviews, observations, and document studies. The research results revealed that the challenges in implementing inclusive education include the absence of GPK who individually assist PDBK in class and have qualifications in special education, limited school funding to provide ideal GPK support for students with special needs, lack of parental cooperation regarding the condition of their children with special needs, PDBK's lack of confidence, difficulties in creating Individualized Education Plans (PPI), as well as school facilities and infrastructure.